2018
DOI: 10.1007/s40123-018-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Cyst Masquerading as Inadvertent Bleb After a Scleral-Fixated Intraocular Lens in Marfan Syndrome: A Case Report

Abstract: IntroductionTo present a case of an epithelial inclusion cyst masquerading as an inadvertent bleb in a patient with Marfan syndrome.Case ReportA woman with Marfan syndrome presented with a subluxed crystalline lens in her right eye, which progressively subluxed over the following 2 years. A lensectomy was performed with placement of an anterior chamber intraocular lens (IOL); however, the patient experienced blurred vision and photopsias and preferred IOL explantation. The IOL was removed and a scleral-fixated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Blebs, in most cases are large and more luminous than conjunctival inclusion cysts and have associated conjunctival epithelial edema. 10 Epithelial inclusion cysts are lined by non-keratinized squamous epithelium. The tan colour of these cysts due to keratin and normal IOP due to lack of connection to anterior chamber help differentiate these cysts from blebs.…”
Section: Discussionmentioning
confidence: 99%
“…Blebs, in most cases are large and more luminous than conjunctival inclusion cysts and have associated conjunctival epithelial edema. 10 Epithelial inclusion cysts are lined by non-keratinized squamous epithelium. The tan colour of these cysts due to keratin and normal IOP due to lack of connection to anterior chamber help differentiate these cysts from blebs.…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival cyst was also documented to masquerade as a pseudo-bleb after sclera-fixated IOL implantation in Marfan syndrome. 1 Shanmugam et al 4 described a case of pseudo-bleb secondary to vitrectomy, but that patient was diagnosed with Traboulsi syndrome. UBM has also been employed to describe the anterior segment findings of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that both eyes in our patient, and those of other reported cases, developed cystic ischemic pseudo-blebs despite no exposure to anti-metabolites such as mitomycin C or 5-fluorouracil. 1 , 2 , 3 , 4 , 5 This suggests aqueous dynamics in the subconjunctival space plays a role in bleb morphology. This has been reported as a risk factor for bleb leak after trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important differential diagnosis of conjunctival cysts is filtering blebs [2,16]. Gosalia NR., et al have reported a case of inclusion cyst masquerading as an inadvertent bleb in a patient with Marfan's syndrome due to abnormal sclera [23]. Gonioscopy helps differentiate the etiology of the cyst, whether due to Trabeculectomy or the mSICS surgery, by viewing the fish mouthing of the scleral tunnel [13].…”
Section: Managementmentioning
confidence: 99%